Deep Brain Stimulation for Obsessive–Compulsive Disorder: A Long Term Naturalistic Follow Up Study in a Single Institution - Holland, Marshall T.; Trapp, Nicholas T.; McCormick, Laurie M.; Jareczek, Francis J.; Zanaty, Mario; Close, Liesl N.; Beeghly, James; Greenlee, Jeremy D.W. (Frontiers in Psychiatry, 2020)
Introduction: Deep brain stimulation (DBS) is a proven, effective tool in the treatment of movement disorders. Expansion of indications for DBS into the realm of neuropsychiatric disorders, especially obsessive-compulsive disorder (OCD), has gained fervent interest, although data on appropriate clinical utilization remains limited. Methods: A retrospective, naturalistic study followed nine severely affected OCD patients (average YBOCs score before implantation 34.2 ± 2.5) treated with DBS of ventral capsule/ventral striatum, with average follow up of 54.8 months. Results: With chronic stimulation (years), a majority of the patients achieved significant benefits in obsessive-compulsive and depressive symptoms. Six patients experienced periods of OCD remission following implantation. Four of the six responders required more than 12 months to achieve response. Relief of major depressive symptoms occurred in four out of six patients with documented co-morbid depression. Settings required to achieve efficacy were higher than those typically utilized for movement disorders, necessitating increased impulse generator (IPG) battery demand. We found patients benefited from conversion to a rechargeable IPG to prevent serial operations for IPG replacement. For patients with rechargeable IPGs, the repetitive habit of recharging did not appear to aggravate or trigger new obsessive-compulsive behaviors or anxiety symptoms. Conclusions: Our study supports and builds upon other research suggesting that DBS for OCD in a real world setting can be implemented successfully and provide long-term benefit for severely affected OCD patients. Optimal patient selection and DBS programming criteria are discussed. The use of rechargeable IPGs appears to be both cost effective and well-tolerated in this population.